Action Speech Teacher Directives in Interaction Indonesian Language Learning for Class VII - Yesi Oktaviani; Irma Suryani; Deri Rachmad Pratama (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2025)
Study This aiming For to reveal and describe various type act speak directives used by teachers in the interaction process learning eye Indonesian language lessons in class VII SMPN 10 Bayung Lencir , Musi Banyuasin Regency . In the research This give Contribution new in field study pragmatic learning Indonesian , especially related use act speak teacher directives in interaction within​ class . Research This use method descriptive qualitative with approach pragmatics . The data studied in the form of speech directives delivered by the teacher during activity learning ongoing . The data sources in study This is sentences that contain element act speak directives spoken by the Indonesian language teacher in class The data collection was carried out through Free Listening and Speaking (SBLC) technique . While that , data analysis was carried out through a number of stages , namely data collection , data reduction , data presentation , and data extraction conclusion . Based on results research , found six form act speak directives , namely : requests , questions , orders , prohibitions , giving permission , and advice. Speech request covers begging , inviting , and requesting . Speech question covers interrogate and ask . Speech order covers command , direct , demand , wish , instruct and regulate . Speech prohibition covers restrict and prohibit . Speech giving permission covers agree , forgive , allow , and grant . Speech advice covers suggest and advise. Penelitian ini bertujuan untuk mengungkap dan mendeskripsikan berbagai jenis tindak tutur direktif yang digunakan oleh guru dalam proses interaksi pembelajaran mata pelajaran Bahasa Indonesia di kelas VII SMPN 10 Bayung Lencir, Kabupaten Musi Banyuasin. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan pragmatik. Data yang dikaji berupa tuturan direktif yang disampaikan oleh guru selama kegiatan pembelajaran berlangsung. Adapun sumber data dalam penelitian ini adalah kalimat-kalimat yang mengandung unsur tindak tutur direktif yang diucapkan oleh guru Bahasa Indonesia di kelas tersebut. Pengumpulan data dilakukan melalui teknik Simak Bebas Libat Cakap (SBLC). Sementara itu, analisis data dilakukan melalui beberapa tahapan, yakni pengumpulan data, reduksi data, penyajian data, dan penarikan simpulan. Berdasarkan hasil penelitian, ditemukan enam bentuk tindak tutur direktif, yaitu: permintaan, pertanyaan, perintah, larangan, pemberian izin, dan nasihat.Tuturan permintaan mencakup memohon, mengajak, dan meminta. Tuturan pertanyaan mencakup mengintrogasi dan bertanya. Tuturan perintah mencakup mengomando, mengarahkan, menuntut, menghendaki, mengintruksikan dan mengatur. Tuturan larangan mencakup membatasi dan melarang. Tuturan pemberian izin mencakup menyetujui, memaafkan, memperbolehkan, dan menganugrahi. Tuturan nasihat mencakup menyarankan dan menasehati.